A facile and green approach for the synthesis of spiro[naphthalene-2, 5′-pyrimidine]-4-carbonitrile via a one-pot three-component condensation reaction using DBU as a catalyst. Issue 2 (23rd December 2015) - Rajeswari, M.; Saluja, Pooja; Khurana, Jitender M.
Abstract : A series of novel spiro[naphthalene-2, 5′-pyrimidine]-4-carbonitriles were synthesized using 1, 3-dimethylbarbituric acid, aldehydes and cyclohexylidene malononitrile in presence of DBU. The structures were confirmed by spectral data and X-Ray crystallography. Abstract : A series of functionalized spiro[naphthalene-2, 5′-pyrimidine]-4-carbonitrile derivatives were synthesized using 1, 3-dimethylbarbituric acid, aldehydes and cyclohexylidene malononitrile in the presence of DBU. The structures were confirmed by spectral data. X-Ray crystallographic studies of one of the compounds confirmed the structure. The crystal packing shows eight molecules in a single unit cell. The crystal structure also revealed intermolecular and intramolecular hydrogen bonding. Mild reaction conditions, high yields, short reaction time and easy separation are some of the salient features of the present protocol.